Dynamic change of bacterial diversity, metabolic pathways, and flavor during ripening of the Chinese fermented sausage - Wang, Ji; Aziz, Tariq; Bai, Ruxue; Zhang, Xin; Shahzad, Muhammad; Sameeh, Manal Y.; Khan, Ayaz Ali; Dablool, Anas S.; Zhu, Yingchun (Frontiers in Microbiology, 2022)
Chinese fermented sausage is a famous fermented meat product with a complex microbiota that has a potential impact on flavor and quality. In this study, Lactobacillus plantarum MSZ2 and Staphylococcus xylosus YCC3 were used as starter cultures to investigate the change in bacterial diversity, metabolic pathways, and flavor compounds during the ripening process of fermented sausages. High-throughput sequencing technology and headspace solid-phase microextraction-gas chromatography–mass spectrometry (HS-SPME-GC/MS) were applied for characterizing the profiles of bacterial diversity, metabolic pathways, and flavor compounds in sausage samples on days 0, 6, and 12 during ripening. Results showed that Lactobacillus, Staphylococcus, Lactococcus, Leuconostoc, and Weissella were the most abundant bacterial genera found in the sausage samples during all stages of fermentation. Functional prediction reveals the abundance of 12 different metabolic pathways, the most important pathways are carbohydrate metabolism, nucleotide metabolism, lipid metabolism, and amino acid metabolism. A total of 63 volatile compounds were successfully identified in fermented sausage samples. Correlational analysis demonstrated that Staphylococcus and Leuconostoc were closely related to the formation of flavor compounds. Therefore, the present study may provide guidance for future use of microbiota to improve flavor, quality, and preservation of fermented sausages.